Las revistas de Biblioteconomía y Documentación en el siglo XIX: «El bibliotecario y el trovador esp - López García, Ana Belén (Documentación de las Ciencias de la Información, 2004)
«El Bibliotecario y el trovador español», magazine specilized in libraryanship and Documentation, began to be printed on the f irst of May in 1841 and had been published until the 18 of August of the same age in Spain, although the publication was continued in Brussels under the same title. The aims of the magazine are gathered in their f irst number. The mention to the origin of the libraires stands out, descried in the articles of his publiction D. Basilio Sebastián Castellanos.
Keywords: Periodicals/ Library and Information Science/ «El bibliotecario y el trovador español»